The Impacts of Community-Driven Development Program in Conflict-Affected Regions: Evidence from Cambodia - Jung, Jaehyun; Kim, Tae Jong; Kim, Booyuel (Asian International Studies Review, 2024)
This study evaluates the effects of the Cambodia Rural Development Program, specifically focusing on income generation and social capital. By employing a differencein-differences framework and propensity score matching, the study finds a statistically significant positive impact on income, primarily driven by increased engagement in regular income-generating activities. However, the study also finds that the program has a limited effect on village-level collective actions, social cohesion, and perceived safety while inadvertently discouraging financial contributions to community projects. Additionally, trust between villagers and government officials remains unchanged. Heterogeneous analyses reveal the ineffective participation of trauma-experienced subgroups, highlighting the need for tailored approaches in conflict-affected regions.